Analisis Prilaku Konsumsii Terhadap Kehadiran Digital Payment - Suryani, Mardian (AGHNIYA: Jurnal Perbankan Syari'ah, 2021)
Digital payment is a payment method that has grown rapidly. This digital payment has protection in storing money and transaction costs, so many people are interested in using digital payment applications. The focus of the research examined in this thesis: 1. How are digital payments used as a means of payment by STIESNU Bengkulu Economics students? 2. What is the consumption behavior with the presence of digital payments as a means of payment by STIESNU Bengkulu Sharia Economics students? The objectives of this research: 1. Explain digital payments as a means of payment by STIESNU Bengkulu Sharia Economics students. 2. Describe the shift in consumption patterns with the presence of digital payments as a means of payment by STIESNU Bengkulu Economics students. The method used in this research is field research using a descriptive qualitative approach. This research was conducted using 3 techniques, namely observation, interviews and documentation. The research results in this study are as follows: first, the use of digital payments for Economics students at STIESNU Bengkulu was well received. Because digital payments provide easy transactions for users, the consumption behavior of STIESNU Bengkulu Sharia Economics students towards the presence of digital payments has increased in usage.